2021
DOI: 10.1002/cptc.202000305
|View full text |Cite
|
Sign up to set email alerts
|

Can Hydrated Electrons be Produced from Water with Visible Light?

Abstract: Ab initio computational methods are employed to explore whether hydrated electrons can be produced by the photodetachment of the excess hydrogen atom of the heptazinyl radical (HzH) in finite-size HzH•••(H 2 O) n clusters. The HzH radical is an intermediate species in the photocatalytic oxidation of water with the heptazine (Hz) chromophore. Hz (heptaazaphenalene) is the monomer of the ubiquitous polymeric wateroxidation photocatalyst graphitic carbon nitride (g-C 3 N 4 ). The energy profiles of minimum-energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…Photodissociation of HzH radicals to yield Hz and free H atoms is one possibility. Photoexcitation of HzH radicals in aqueous environments can lead to the formation of transient hydrated electrons 51 which have higher reduction potentials than free hydrogen atoms. 52 Another possibility, considered herein, is the formation of doubly reduced Hz molecules via the spontaneous disproportionation of HzH radicals.…”
Section: Hzh Hzhmentioning
confidence: 99%
“…Photodissociation of HzH radicals to yield Hz and free H atoms is one possibility. Photoexcitation of HzH radicals in aqueous environments can lead to the formation of transient hydrated electrons 51 which have higher reduction potentials than free hydrogen atoms. 52 Another possibility, considered herein, is the formation of doubly reduced Hz molecules via the spontaneous disproportionation of HzH radicals.…”
Section: Hzh Hzhmentioning
confidence: 99%
“…In particular, heptazine (heptaazaphenalene) is the monomer of the well-known polymeric photocatalyst graphitic carbon nitride (g-C 3 N 4 ) which is widely employed in current water-splitting research. It has recently been shown that a chemically and photochemically stable derivative of heptazine, tri-anisole-heptazine, can photooxidize water under irradiation at 365 nm, yielding the heptazinyl radical . Computational studies indicate that hydrated electrons can be generated by photodissociation of the heptazinyl radical in an aqueous environment with near-visible light . Since the absorption bands of organic chromophores can be systematically tuned over a wide range by chemical modification, it may be possible to synthesize organic photocatalysts that can generate hydrated electrons from water with visible light.…”
Section: Discussionmentioning
confidence: 99%
“…45 Computational studies indicate that hydrated electrons can be generated by photodissociation of the heptazinyl radical in an aqueous environment with near-visible light. 46 Since the absorption bands of organic chromophores can be systematically tuned over a wide range by chemical modification, it may be possible to synthesize organic photocatalysts that can generate hydrated electrons from water with visible light.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, excitation of the 2 πσ* state of HzH in aqueous environments can lead to the formation of hydrated electrons. Recent calculations predict a barrierless reaction path devoid of conical intersections for the photoinduced formation of the H 3 O···(H 2 O) n −1 radical in HzH···(H 2 O) n clusters . The hydrated H 3 O radical is a convenient finite-size model of the hydrated electron in bulk water. , The lifetime of the hydrated electron at ambient conditions is of the order of a microsecond, which is sufficient for effective diffusion-controlled reactions.…”
Section: Discussionmentioning
confidence: 99%